2014
DOI: 10.4238/2014.april.25.7
|View full text |Cite
|
Sign up to set email alerts
|

Efficient production of transgenic melon via Agrobacterium-mediated transformation

Abstract: Oriental melon (Cucumis melo L. var. makuwa) is an important fruit for human consumption. However, this plant species is one of the most recalcitrant to genetic transformation. The lack of an efficient in vitro system limits the development of a reproducible genetic transformation protocol for Oriental melon. In this study, an efficient transgenic production method for Agrobacterium-mediated transformation using cotyledon explants of Oriental melon was developed. Cotyledon explants were pre-cultivated for two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…by using co-cultivation with Agrobacterium (Table 3). Some improved protocols have been lately reported in melon (Bezirganoglu et al 2014), cucumber (Wang et al 2015) and watermelon (Liu et al 2016). In the cucurbitaceous species, an efficient regeneration procedure via somatic embryogenesis from embryogenic calli, developed from leaf explants, has also been recently published (Vinoth & Ravindhran, 2015).…”
Section: Genetic Engineering For Fruit Quality and Yield Enhancementmentioning
confidence: 99%
“…by using co-cultivation with Agrobacterium (Table 3). Some improved protocols have been lately reported in melon (Bezirganoglu et al 2014), cucumber (Wang et al 2015) and watermelon (Liu et al 2016). In the cucurbitaceous species, an efficient regeneration procedure via somatic embryogenesis from embryogenic calli, developed from leaf explants, has also been recently published (Vinoth & Ravindhran, 2015).…”
Section: Genetic Engineering For Fruit Quality and Yield Enhancementmentioning
confidence: 99%
“…Various (young) explants have been generally inoculated with Agrobacterium followed by regeneration through shoot organogenesis, but transformation efficiency varied largely with the genotype used ( Klocke et al, 2010 ; Manamohan et al, 2011 ). Some improvements in the protocol have been lately reported for melon ( Bezirganoglu et al, 2014 ; Zhang et al, 2014 ), cucumber ( Wang et al, 2015 ), Cucurbita spp. ( Nanasato et al, 2013 ), and watermelon ( Liu et al, 2016 ).…”
Section: Regeneration and Transformationmentioning
confidence: 99%
“…DNA content and changes in chromosome number have been reported in several transgenic melon subspecies through ow cytometric analysis. In most reports concerning melon transformation, the ploidy levels of the transgenic lines were not speci ed (Switzenberg et al, 2014;Bezirganoglu et al, 2014) and in some cases a high percentage of instability was observed. In one of the latest melon transformation expriments (GarciaAlmodovar et al, 2017), a large number of transgenic plants became tetraploid, whereas the diploid level decreased signi cantly in tranformed melons when the infected explants grew from seedling.…”
Section: Introductionmentioning
confidence: 99%